Surgical management of lifebuoy cataract - Rym Maamouri; Meriem Ouederni; Zeineb Gharbi; Monia Cheour (Indian Journal of Ophthalmology, 2023)
Lifebuoy cataract is a rare form of congenital cataract with anatomical characteristics. Herein, we present a case of an otherwise healthy 42-year-old female with a long-standing history of blurred vision. Examination showed the presence of esotropia and bilateral horizontal nystagmus. Visual acuity was limited to light perception in both eyes. Slit-lamp examination showed a calcified lens capsule with the absence of lens material in the right eye and the presence of an annular cataract in the left eye, corresponding to a unilateral lifebuoy cataract. She underwent cataract surgery with intraocular lens implantation. We report the clinical findings, anterior segment optical coherence tomography (AS-OCT), and surgical management tips. We noticed that during surgery, both anterior capsulorhexis and central membrane removal were the most challenging steps due to the absence of central nucleus and the strong adherence of central membrane to the anterior hyaloid.